Realistic simulation of mixed sea using multiple spectrum-based wave systems. (March 2020) - Park, Sekil; Park, Jinah
The sea has a very wide, irregular, and continuously changing surface and is usually a mixed sea composed of several wave systems. Each wave system is generated from different locations and conditions and has its own characteristics. The Fourier domain approach using sea wave spectra is an effective technique for the realistic simulation of sea surfaces in real time, but the conventional Fourier domain approach cannot independently simulate the characteristics of each wave system. In this paper, we propose a realistic and real-time simulation method of the mixed sea using multiple spectrum-based wave systems for maritime simulators. We recognize the importance of the visual and physical contributions of each wave system and faithfully reproduce all wave systems in the mixed sea. In order to simulate the mixed sea, our method generates and combines multiple spectrum-based wave systems using adaptive spectral sampling of the separated spectrum of the multi-peaked spectrum. The unique characteristics of each wave system can be set independently through spectral parameters, sampling number and range, wave direction and spread, and the shape factor of waves. The proposed method also supports the smooth transition between sea states, such as wind sea, swell, and mixed sea. Through the experiments, we verify that the proposed method effectively reflects sea wave spectra and the reproduced sea has very similar statistical characteristics to the actual sea. Experimental results also show that our approach can simulate the mixed sea, which has high-frequency wind sea and low-frequency swell.